Оцінка ефективності технології профілактики плоскостопості в юних баскетболістів - Строганов, Сергій; Stroganov, Sergey (Східноєвропейський національний університет ім. Лесі Українки, 2013)
Виявлено, що заняття спортом не гарантують відсутність порушень у стані стопи. Установлено, що профілактика плоскостопості в спортсменів 9–10 років, які спеціалізуються в баскетболі, є актуальним завданням на початковому етапі багаторічного тренування. Запропоновано технологію профілактики порушень опорно-ресорних властивостей стопи юних баскетболістів, яка передбачає ранню діагностику стану рухової функції стопи та впровадження комплексів спеціально підібраних вправ у тренувальний процес. Доведено, що впровадження технології сприяло підвищенню якості виконання спортсменами основних технічних прийомів. It was found that exercises do not guarantee the absence of irregularities in foot condition. It was found that prevention of flatfoot of athletes of 9–10 years, specializing in basketball, is an urgent task at the initial stage of long-term training. A technology for the prevention of musculoskeletal disorders of the foot of spring properties of young basketball players, which provides for the early diagnosis of the motor function of the foot and introduction of specially selected exercises in the training process was proposed. The experiment involved 25 young basketball players who had found a flattening of the foot and 17 athletes with normal foot. In this paper, the method of tensor dynamometry is used to assess the quality of specific motor tests,that proves, that the introduction of technology has contributed to improving the quality of the athletes performing the basic techniques.
Evaluating the Effectiveness of Prevention Technologies of Flatfoot of Young Basketball Players
Keywords: баскетбол; навантаження; стопа; порушення; плоскостопість; технологія; профілактика; basketball; violations; flat; technology; prevention